2021
DOI: 10.1177/25158414211009007
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors affecting macular hole closure types

Abstract: Purpose: In this study, we aimed to evaluate the relationship between macular hole closure types assessed by optical coherence tomography (OCT) and the preoperative prognostic factors. Materials and methods: In total, 183 patients who underwent pars plana vitrectomy and internal limiting membrane peeling for idiopathic macular hole between August 2014 and August 2019 were reviewed retrospectively. The preoperative measurements of the macular hole including minimum linear diameter (MLD), basal hole diameter (BH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Also, the preoperative MH height was significantly higher in the InFlap group, which was purely by chance as the allocation was completely randomized. A recent study by Gümüş et al [ 20 ] did not find any significant influence on the closure rate by vertical MH measurements as compared to horizontal MH measurements.…”
Section: Discussionmentioning
confidence: 84%
“…Also, the preoperative MH height was significantly higher in the InFlap group, which was purely by chance as the allocation was completely randomized. A recent study by Gümüş et al [ 20 ] did not find any significant influence on the closure rate by vertical MH measurements as compared to horizontal MH measurements.…”
Section: Discussionmentioning
confidence: 84%
“…In a retrospective study done by Demir et al . [ 18 ] on 183 patients, BD was 924.72 ± 341.58 mm (range: 118–2148) in eyes observed to have type-1 closure and 1153.58 ± 399.86 mm (range: 401–2303) with type-2 closure ( P = 0.04), and hole height was noted to be 464.5 ± 92.86 mm in type-1 closure and 506.67 ± 196.27 mm in type-2 closure ( P = 0.239).…”
Section: Discussionmentioning
confidence: 99%
“…Yao et al [3] showed better visual and anatomical results with the 4-disc diameter peeling group compared to the 2-disc diameter group in macular holes less than 500 microns. The size of ILM peeled area was found to be a predictor in anatomical success of macular hole surgery [4] . ILM plays an important role as a scaffold for cellular proliferation and ERM formation [5] .…”
Section: Dear Editormentioning
confidence: 98%